PENGARUH KEBERADAAN KOMITE AUDIT PADA HUBUNGAN POSITIF RISIKO PERUSAHAAN DENGAN KONSERVATISMA AKUNTANSI - Diah Asrida, Putu; Widanaputra, A.A.G.P; Gede Wirama, Dewa (Buletin Studi Ekonomi, 2016)
The Impact of the Existence of the Audit Committees to the Relationship Between Company’s risk and Conservatism Accounting. The aim of the research is to examine the impact of the existence of the audit committees to the relationship between company’s risk and conservatism accounting. The audit committee is measured by proxy the number of audit committee members while the company’s risk was proxy with debt to equity ratio and accounting conservatism measured by the accrual value. Sample in this research are companies listed to stock exchanges of Indonesia which publishes annual report from 2005 to 2009 and who applied conservative accounting as well as having an audit committee. The testing of hypothesis in this research is used moderated regression analysis (MRA). The result of hypothesis test indicated that audit committees affect the positive relationship between company’s risk and conservatism accounting. The higher of the company’s risk, then the audit committee will recommend the application of conservative accounting. This is proving that the existence of audit committees within the company can minimize the agent’s problem. Keywords: audit committee, company’s risk and accounting conservatism
Keywords: audit committee, company’s risk and accounting conservatism